Serum Lipid Levels and Treatment Outcomes in Women Undergoing Assisted Reproduction: A Retrospective Cohort Study - Cai, Wang-Yu; Luo, Xi; Chen, Erxidi; Lv, Houyi; Fu, Kaiyou; Wu, Xiao-Ke; Xu, Jian (Frontiers in Endocrinology, 2021)
Objective: To evaluate associations between serum lipid levels and treatment outcomes in women undergoing assisted reproduction. Materials and methods: The study included 2011 women who underwent in vitro fertilization/intracytoplasmic sperm injection with fresh embryo transfer. Serum lipid evaluation included total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high density lipoprotein cholesterol (HDL-C), and triglycerides (TG). Ovarian stimulation outcomes included endometrial thickness and the number of oocytes retrieved, and reproductive outcomes included live birth, clinical pregnancy, and miscarriage. Results: Higher HDL-C quartiles were associated with more oocytes retrieved. Lower TC (quartile 1 odds ratio [OR] 1.59 [1.21–2.08], quartile 3 OR 1.36 [1.04–1.77]), LDL-C (quartile 1 OR 1.41 [1.07–1.86]), and TG (quartile 2 OR 1.39 [1.06–1.84]) were independently associated with clinical pregnancy after adjusting for potential confounders. Lower LDL-C (quartile 1 OR 2.22 [1.58–3.13], quartile 2 OR 1.78 [1.27–2.50], quartile 3 OR 1.51 [1.07–2.13]), TC (quartile 1 OR 1.39 [1.00–1.93]), TG (quartile 1 OR 1.44 [1.03–2.03], quartile 2 OR 1.46 [1.04–2.04], quartile 3 OR 1.44 [1.04–1.99]), and higher HDL-C (quartile 2 OR 0.71 [0.51–0.99]) were independently associated with live birth. Higher LDL-C (quartile 1 OR 0.44 [0.30–0.66], quartile 2 OR 0.49 [0.33–0.73], quartile 3 OR 0.63 [0.43–0.94]) and lower HDL C (quartile 1 OR 1.60 [1.07–2.39]) were independently associated with miscarriage. Conclusions: Serum lipid levels were associated with treatment outcomes in women undergoing assisted reproduction.